(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to examine some of the characteristics of students who prefer Pamukkale University Faculty of Dentistry and Adnan Menderes University, to investigate the level of knowledge about the specialty, to determine the expectations of the students from the specialty, and to create a guide for the applicants. Material and Methods: A survey was applied including questions about their gender, level of expertise, which specialty they would prefer and the most important factor in this preference, their expectations from the specialty at the time of graduation and whether they found the education received in the faculty adequate for entering the specialty exam; to all students in the 1st 2nd and 3rd grades of Pamukkale University Faculty of Dentistry and to all students in the 1st 2nd 3rd 4th and 5th grades of Adnan Menderes University Faculty of Dentistry.Results: According to results, of our study, 76.1% of the students thought that the education they received in the faculty was not sufficient to pass the Specialty Examination in Dentistry (SED). However, 76.1% of the students stated that they were planning to go to the private teaching institutions during the preparation process for SED. In addition, the most preferred specialty is Orthodontics with 31.2%, followed by Oral, Maxillofacial and Maxillofacial Surgery with 31%. They stated that situations such as the desire for academic career and the comfort of working conditions were the most important factors in choosing the specialty.Conclusion: As a result, it was found that the students who choose the faculty of dentistry, which have a long and challenging education process both theoretically and practically, not enough knowledge about SED and therefore it is important getting the right information about SED and specialty education.